2018
DOI: 10.3329/bjms.v17i1.35276
|View full text |Cite
|
Sign up to set email alerts
|

Onosma bracteatum wall: A Potent analgesic agent

Abstract: AbstrtactBackground: This study was aimed to find out the central and peripheral analgesic activity of hydro methanolic extract of aerial parts of Onosma bracteatum. Material and methods: The central and peripheral analgesic activity is evaluated by tail flick test and acetic acid induced writhing test at the doses of 50, 100, 250 and 500mg/kg body weight respectively in animal models. Results: The results obtained from Tail flick test revealed that O. bracteatum possesses potent analgesic effects by inducing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 2 publications
0
11
0
Order By: Relevance
“…These polyphenols have the antioxidant, antimutagenic and chemopreventive properties that might help to protect and conserve the constancy of genome (Mehta et al, 2010;Rodrıǵuez-Garcıá et al, 2019). Previous studies have reported the potential of Onosma genus as antioxidant compounds and their use in averting numerous pharmacological situations (Naz et al, 2006;Ebrahimzadeh et al, 2010;Ahmad et al, 2013;Imran et al, 2018;Farooq et al, 2019). In the current study, we investigated the antioxidant, antimutagenic, genoprotective, and hepatoprotective properties of Obeth from Onosma bracteata along with evaluation of the expression of proteins involved in the inflammation and apoptotic induction in in vivo studies using male Wistar rats.…”
Section: Discussionmentioning
confidence: 99%
“…These polyphenols have the antioxidant, antimutagenic and chemopreventive properties that might help to protect and conserve the constancy of genome (Mehta et al, 2010;Rodrıǵuez-Garcıá et al, 2019). Previous studies have reported the potential of Onosma genus as antioxidant compounds and their use in averting numerous pharmacological situations (Naz et al, 2006;Ebrahimzadeh et al, 2010;Ahmad et al, 2013;Imran et al, 2018;Farooq et al, 2019). In the current study, we investigated the antioxidant, antimutagenic, genoprotective, and hepatoprotective properties of Obeth from Onosma bracteata along with evaluation of the expression of proteins involved in the inflammation and apoptotic induction in in vivo studies using male Wistar rats.…”
Section: Discussionmentioning
confidence: 99%
“…Medicinal plants are important elements of indigenous medical systems in Palestine as well as in other developing countries. Complementary and alternative medicine utilization in Palestine are common elsewhere, whereas other types were unique to this area 2,55 . There has been an increasing incidence of multiple antibiotic resistances in human pathogenic microorganisms in recent years, largely due to indiscriminate use of commercial antibacterial drugs commonly employed in the treatment of infectious diseases, which have led to the emergence of new bacterial strains that are multi-drug resistant which have resulted in increase in morbidity, mortality and creates enormous health problems.…”
Section: Introductionmentioning
confidence: 99%
“…O. bracteatum is commonly used as a demulcent, alterative, diuretic, immunity enhancer and spasmolytic and as a major constituent of various Ayurvedic formulations for the treatment of hypertension, leprosy, rheumatism and asthma [12,13]. Pharmacological studies on O. bracteatum reported that it has antibacterial, analgesic, antioxidant and wound healing activities [14,15,16]. Additionally, it has acetyl-cholinesterase and NADH oxidase inhibitory activities.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it has acetyl-cholinesterase and NADH oxidase inhibitory activities. It also contains carbohydrates, fatty acids, flavonoids, tannins, glycosides and phenolic constituents [12,15].…”
Section: Introductionmentioning
confidence: 99%